Structural Analysis of Female Teachers' Burnout based on Professional Ethics and Participatory Management - Kamelia Seyed Jalali, Dr. Zarrin Daneshvar, Dr. Assadollah Khadivi, Dr. Behnam Talebi (Drugs and Cell Therapies in Hematology, 2021)
This study was aimed to analyze the structural burnout of female teachers at all girl high schools in Tabriz considering professional ethics and participatory management as contributing factors. This was a descriptive-correlational study based on causal structural equation modeling (SEM). Participants were 126 teachers having less than 10 years of work experience. The sample size was estimated at 100 using the Morgan table and stratified random sampling. Data were collected through Ghramaleki Professional Ethics Questionnaire, Maslach Burnout Inventory (MBI), and Shagholi Participatory Management Questionnaire. The content validity and reliability of the questionnaires were confirmed. PLS Path analysis-SEM results showed significant structural relationships between professional ethics and burnout, and professional ethics and participatory management in female teachers.